Clinical profile of patients with cutaneous disorders - Singh, Khileshwar; Dhruv, Kamlesh; Thakur, Amit (International Journal of Research in Medical Sciences, 2017)
Background: 50-75% of all the patients who are on dialysis suffer from significant xerosis. But the exact cause is difficult to trace. Acquired ichthyosis is seen in some patients. Atrophy of sebaceous glands is seen in patients with uraemia. Such patients also show overall decrease in sweet volume. Objective was to study the clinical profile of patients with cutaneous disorders. Methods: A hospital based prospective study was carried out from September 2012 to February 2013 at a tertiary care centre of Late Baliram Kashyap memorial government medical college, Jagdalpur, Chhattisgarh, India. A total of 50 patients with cutaneous disorders were studied with respect to their clinical profile. Patients not willing to participate in the present study as per the protocol were excluded from the study. But patients giving their willingness to participate in the present study as per the protocol of the study were included in the study. Results: The males constituted 58% of the total cases and the females constituted 42% of the total cases. Maximum patients were seen in the fourth and fifth decade of their life i.e. 24% followed by the age group of 31-40 years i.e. 22%. The most common cutaneous manifestation was pruritus in 24% of cases followed by xerosis in 16% of cases. Next most common cutaneous manifestation was Tinea versicolor inn 14% of cases followed by oral candidiasis in 8% of cases and scabies were seen in 6% of cases. Both among males and females, pruritus was the most common skin lesion seen. Conclusions: The most common cutaneous lesion found in the present study was pruritus in 24% of cases followed by xerosis (16%), Tinea versicolor (14%), oral candidiasis (8%) and scabies in 6% of cases. Cases of nail changes, herpes zoster, Tinea cruris, hyper pigmentation, folliculitis, Exfoliative dermatitis, and Kyrle’s disease, Vitiligo, Melisma and Keloid were also seems.